An exploration of health professional's perceptions of the role of clinical psychologists - Zitianellis, Marina Sophia (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
The South African government has initiated the transformation of health services in the country towards primary health care (PHC) in order to provide comprehensive care to individuals and families. The move to PHC involves an increased need for collaboration between health professionals. It is proposed that for effective team-work to take place, an understanding of the roles and functions of team members is imperative in providing quality mental health care. This study explored health professionals' perceptions of the role and function of clinical psychologists working as part of a health care team in a community context. Three focus groups and three individual interviews were conducted with social workers, nurses and doctors. The data was then processed and analysed using a grounded theory method. The research highlighted the importance of knowledge, and how this affects referrals, perceptions, inter-professional relations and the perceived usefulness of clinical psychology and clinical psychologists. What is of significance is the potential power that the health professionals have as gatekeepers between the general public and clinical psychologists.
Keywords: Community health services -- South Africa; Community mental health services -- South Africa; Medical personnel -- South Africa -- Attitudes; Primary health care -- South Africa; Clinical psychologists